CORRELATION OF THE MAIN SUBTYPES OF PLANTLETS MYCORHIZA AND PARENTAL SPECIES OF EUROPEAN FIR-TREE, SCOTCH PINE AND ENGLISH OAK IN THE CONDITIONS OF VARIOUS LEVEL OF RADIOACTIVE POLLUTION - I. Y. Adamovich (Новые технологии, 2017)
Stimulant effect of radiation on the mycorrhizal behavior of seedlings and parental individuals of Scotch pine, English oak tree, European fir at MED = 120 ... 270 microR / h and inhibitory effect at MED = 500 ... 1000 mcR / h is considered.